The match : "savior siblings" and one family's battle to heal their daughter - Whitehouse, Beth, 1961- (Beacon Press, 2010)
My Sister's Keeper in nonfiction: a family's real-life struggle to cure their daughter by creating her genetic match Katie Trebing was diagnosed at three months old with Diamond Blackfan anemia, a rare form of anemia that prevents bone marrow from producing red blood cells. Even with a lifetime of monthly blood transfusions, she faced a poor prognosis. Pulitzer Prize'winning journalist Beth Whitehouse follows the Trebings as they make the decision to create a genetically matched sibling using preimplantation genetic diagnosis (PGD) and in vitro fertilization, and proceed with a risky bone-marrow transplant that could kill their daughter rather than save her. The Match is a timely and provocative look at urgent issues that can only become more complex and pressing as genetic and reproductive technologies advance. From the Trade Paperback edition.